Soil enzyme activities, microbial communities, and carbon and nitrogen availability in organic agroecosystems across an intensively-managed agricultural landscape - Bowles, Timothy M.; Acosta-Martínez, Veronica; Calderón, Francisco; Jackson, Louise E. (Soil biology & biochemistry, 2014)
Variability in the activity and composition of soil microbial communities may have important implications for the suite of microbially-derived ecosystem functions upon which agricultural systems rely, particularly organic agriculture. An on-farm approach was used to investigate microbial communities and soil carbon (C) and nitrogen (N) availability on 13 organically-managed fields growing Roma-type tomatoes, but differing in nutrient management, across an intensively-managed agricultural landscape in the Central Valley of California. Soil physicochemical characteristics, potential activities of nine soil enzymes involved in C, N, phosphorus (P), and sulfur (S) cycling, and fatty acid methyl esters (FAMEs) were measured during the growing season and evaluated with multivariate approaches. Soil texture and pH in the 0–15 cm surface layer were similar across the 13 fields, but there was a three-fold range of soil C and N as well as substantial variation in inorganic N and available P that reflected current and historical management practices. Redundancy analysis showed distinct profiles of enzyme activities across the fields, such that C-cycling enzyme potential activities increased with inorganic N availability while those of N-cycling enzymes increased with C availability. Although FAMEs suggested that microbial community composition was less variable across fields than enzyme activities, there were slight community differences that were related to organic amendments (manure vs. composted green waste). Overall, however, the general similarity among fields for particular taxonomic indicators, especially saprophytic fungi, likely reflects the high disturbance and low complexity in this landscape. Variation in potential enzyme activities was better accounted for with soil physicochemical characteristics than microbial community composition, suggesting high plasticity of the resident microbial community to environmental conditions. These patterns suggest that, in this landscape, differences in organic agroecosystem management have strongly influenced soil nutrients and enzyme activity, but without a major effect on soil microbial communities. The on-farm approach provided a wide range of farming practices and soil characteristics to reveal how microbially-derived ecosystem functions can be effectively manipulated to enhance nutrient cycling capacity. •Soil microbial community activity and composition was investigated in 13 organic fields.•C-cycling enzyme activities increased with inorganic N availability.•N-cycling enzyme activities increased with C availability.•Microbial community composition was differentiated by organic amendment applied.